Bilateral blindness due to pterygium: a case report - Azonobi, Richard I.; Udoye, Ezenwa Patrick; Onua, Alfred A. (International Journal of Research in Medical Sciences, 2017)
Although known to cause refractive visual disturbances at some stages, pterygium rarely leads to blindness especially where eye care services are available. This case report presents a 56 year old farmer with advanced pterygia. She reported to the eye clinic after several years of unsuccessful self-medication and refusal to accept an earlier offer of surgical treatment due to fear of surgery. The patient subsequently had surgical excision of both pterygia with visual restoration. The importance of meticulous counseling and health education on the incidence of needless blindness is emphasized.